Cooperativismo e associativismo na produç\~ao agropecuária de menor porte no Brasil - Érica Basílio Tavares Ramos; José Eustáquio Ribeiro Vieira Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– Collective production organizations (cooperatives and associations) can bargain for better prices and lower costs, which increases net revenue, on the one hand, and facilitates the adoption of technologies, on the other. This study seeks to evaluate the impact of family production in Brazil and its relationship with the productive structure. As a hypothesis, it is believed that collective production organizations (cooperatives or producers' associations) contribute to the growth of smaller agricultural production and to the more efficient use of resources. Therefore, first, a production function was estimated, using the local spatial stochastic frontier model, to assess the productive dynamics and the institutional presence of cooperatives and associations in Brazilian municipalities. Then, the sources of technical efficiency of the smaller production were measured. Based on the 2017 Agricultural Census, it was found that the regional percentage of family farming production in cooperatives and associations has a positive effect on the gross value of production and on local development. The results showed that the municipalities in the Northeast have lower technical efficiency than those in the South, Southeast and Midwest. This conclusion is related to the institutional environment, which in the South can promote policies with greater local integration (bottom-up) and which in the Northeast depends on more centralized actions, with low insertion of local institutions (top-down). Variables such as education, technical orientation and precipitation contributed to efficiency gains. Therefore, the promotion of collective arrangements and the inclusion of local institutions are a relevant regional development instrument in the context of productive growth, which in turn increases the technical efficiency of small-scale agricultural production in Brazil.
Keywords: C01; O13; Q1; 330; family farms; small scale production; cooperatives; associations